2013
DOI: 10.1002/jcph.166
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of voclosporin in renal impairment and hepatic impairment

Abstract: Voclosporin is a novel calcineurin inhibitor intended for prevention of organ graft rejection and treatment of lupus nephritis. These studies evaluated the effect of renal or hepatic impairment on pharmacokinetics of voclosporin. Thirty-three subjects were enrolled into 1 of 4 groups based on renal function as defined by creatinine clearance and 18 subjects were enrolled into 1 of 3 groups based on hepatic function defined by Child-Pugh classes. Voclosporin 0.4 mg/kg was administered orally. Geometric mean rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The PK data of voclosporin included the single ascending doses from 0.25 to 4.5 mg/kg, 10 multiple doses of 0.4 mg/kg in an organ impairment study and a control cohort in a drug–drug interaction study. 11 , 12 The PK data for cyclosporine included PK studies of single doses of cyclosporine in healthy Caucasians (350, 700 and 1400 mg) 9 and drug–drug interaction studies with cyclosporine dosed at 300 and 400 mg. 12 , 13…”
Section: Methodsmentioning
confidence: 99%
“…The PK data of voclosporin included the single ascending doses from 0.25 to 4.5 mg/kg, 10 multiple doses of 0.4 mg/kg in an organ impairment study and a control cohort in a drug–drug interaction study. 11 , 12 The PK data for cyclosporine included PK studies of single doses of cyclosporine in healthy Caucasians (350, 700 and 1400 mg) 9 and drug–drug interaction studies with cyclosporine dosed at 300 and 400 mg. 12 , 13…”
Section: Methodsmentioning
confidence: 99%
“…50 Similarly, other data indicate that 40% CN inhibition is achieved with VCS at an AUC of 226 ng × hour/mL, but with a 15% rise in serum creatinine occurs only at a VCS AUC of 3448 ng × hour/mL. 22,50 Ling et al 22 concluded that mild to moderate hepatic impairment resulted in a 1.5-to 2-fold increase in VCS exposure. VCS can be administered safely to patients with mild to moderate renal impairment without dose modification.…”
Section: Vcs Therapeutic Monitoringmentioning
confidence: 97%
“…VCS is a novel CNI intended for the prevention of organ graft rejection and treatment of lupus nephritis. 22 It has a strong immunosuppressant effect by reversible inhibition of T-lymphocyte proliferation and release of cytokines through blocking the cytoplasmic calcium dependent phosphatase. 15 Inside lymphocytes, voclosporin binds to immunophilins forming complexes that inhibit CN.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…There were no clinically relevant effect of age, bodyweight, gender, race, serum albumin, total bilirubin and eGFR on the pharmacokinetics of voclosporin [4,13]. Voclosporin C max and AUC in patients with mild [creatinine clearance (CL cr ) 60-89 mL/min as estimated by Cockcroft-Gault] and moderate (CL cr 30-59 mL/min) renal impairment were similar to those in subjects with normal renal function (CL cr ≥ 90 mL/min) [4,14]. In patients with severe (CL cr < 30 mL/min) renal impairment, voclosporin C max and AUC increased by 1.5-and 1.7-fold, respectively.…”
Section: Pharmacokineticsmentioning
confidence: 99%